PENGARUH PERSEPSI PEGAWAI TENTANG GAYA KEPEMIMPINAN, MOTIVASI KERJA, DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KEJAKSAAN TINGGI - Riska Indah Nurmeilia; Wiedy Murtini; Patni Ninghardjanti (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2020)
This study aims to determine whether: (1) There is a positive and significant influence between employee perceptions of leadership style on the performance of the West Java High Court employees; (2) there is a positive and significant influence between work motivation on the performance of the West Java High Court employees; (3) there is a positive and significant influence between work discipline on the performance of the West Java High Court employees; (4) there is a positive and significant influence between perceptions of leadership style, work motivation, and work discipline simultaneously on the performance of the West Java High Court employees. This research is a research with a quantitative approach with the type of correlational / associative research. The data collection method is done by using a questionnaire. The population in this study amounted to 278 people and the sample in this study amounted to 74 people. The sampling technique in this research is proportional sampling technique with a sample taken of 74 respondents. The data obtained from this study were then processed using the IBM SPSS 24 tool. This analysis includes validity testing, reliability testing, classical assumption tests and hypothesis testing. Based on the research results, H1 shows that the leadership style has a negative and insignificant effect on employee performance, which means that Ho is accepted and H1 is rejected. H2 shows that work motivation has a positive and significant effect on employee performance, which means that Ho is rejected and H3 is accepted. H3 shows that work discipline has the most positive and significant effect on employee performance, which means that Ho is rejected and H2 is accepted. H4 shows that leadership style, work motivation, and work discipline have a simultaneous influence on employee performance, which means that Ho is rejected and H3 is accepted.